Family Planning as a Prerequisite for Siri Marriage (Case Study in Pacentan Village, Tanah Merah District) - Sukron; Jezeri; JK Habibi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to describe a number of cases that occurred in the Pacentan village community, Tanah Merah District, Bangkalan Regency regarding unregistered marriages with the condition of participating in the Family Planning program which is usually called KB. This research is field research using qualitative methods that are descriptive-analytic in nature. The author tries to examine the dynamics of implementing unregistered marriages with the requirement of following family planning from Maslahah Murlah's perspective. The results of this research show that the requirement to participate in family planning for every unregistered marriage is an alternative that has a good impact on men and women who have not yet reached the age of 19 in accordance with the provisions of the applicable marriage law. Family planning functions to plan birth by postponing pregnancy temporarily according to family conditions and reducing the negative impact of unregistered marriages until the marriage is registered at the local KUA which is basically in accordance with positive legal provisions. In this case, the practice of marriage is in accordance with the elements of benefit, namely protecting religion, protecting offspring, and is a general benefit.